Effect of kanglaite on rat cytochrome P450. (July 2015) - Du, Xiaoxiang; Ye, Huizhou; Zhang, Chunxia; Ye, Lei; Lin, Guanyang
Abstract Context: Kanglaite (KLT) is an oily substance extracted from Coix lacryma-jobi Linn. (Cramineae) and has been proved to significantly improve the life span and quality of life of patients, when combined with chemotherapy, radiotherapy, or surgery. Objective: The purpose of this study was to find out whether KLT influences the effect on rat cytochrome P450 (CYP) enzymes (CYP1A2, CYP2B6, CYP2C9, CYP2C19, and CYP3A4) by using cocktail probe drugs in vivo. Materials and methods: A cocktail solution at a dose of 5 mL/kg, which contained phenacetin (20 mg/kg), bupropion (20 mg/kg), tolbutamide (5 mg/kg), omeprazole (20 mg/kg), and midazolam (10 mg/kg), was given as oral administration to rats treated with 7 d intraperitoneal injection of KLT. Blood samples were collected at a series of time-points and the concentrations of probe drugs in plasma were determined by HPLC-MS/MS. The corresponding pharmacokinetic parameters were calculated by the software of DAS 2.0 (SPPS Inc., Chicago, IL). Results: In the experiment, there was a statistically significant difference in the t1/2, Cmax, AUC(0–∞), and CL for phenacetin, bupropion, tolbutamide, omeprazole, and midazolam. Our study showed that treatment with multiple doses of KLT had induction effect on rat CYP1A2, while CYP2B6, CYP2C9, CYP2C19, and CYP3A4 enzyme activities had been inhibited after multiple doses of KLT treatment. Conclusions: KLT can either induce or inhibit activities of CYP. Therefore, caution is needed when KLT is co-administration with some CYP substrates in clinic, which may result in herb–drug interactions.